Measuring justice: defining concepts, developing practice - Armstrong, Sarah (Report, 2020)
This research was funded under a Scottish Government grant call for ‘experiences of justice’, and reviews concepts and measurement techniques for justice experiences. The aims of this project are:to provide an introduction to key frames of justice for Scotland (especially procedural justice and person-centred support);togather and analyse international literature on how justice is defined and measured; and to present and assess various mechanisms for measuring justice experiencesmost applicable to Scotland